Academic Disciplines in the Context of Library Classification: Mapping University Faculty Structures to the DDC and LCC Schemes. Issue 2 (17th February 2022) - Hider, Philip; Coe, Mary
Abstract: We investigated the extent to which the Dewey Decimal Classification (DDC) and the Library of Congress Classification reflect the organizational structures of Australian universities. The mapping of the faculty structures of ten universities to the two schemes showed strong alignment, with very few fields represented in the names of the organizational units not covered at all by either bibliographic scheme. This suggests a degree of universality and "scientific and educational consensus" with respect to both the schemes and academic disciplines. The article goes on to discuss the concept of discipline and its application in bibliographic classification.